Polypharmacology-based approach for screening TCM against coinfection of Mycoplasma gallisepticum and Escherichia coli - Bao, Jiaxin; Wang, Yuan; Wang, Shun; Niu, Dong; Wang, Ze; Li, Rui; Zheng, Yadan; Ishfaq, Muhammad; Wu, Zhiyong; Li, Jichang (Frontiers in Veterinary Science, 2022)
Natural products and their unique polypharmacology offer significant advantages for finding novel therapeutics particularly for the treatment of complex diseases. Meanwhile, Traditional Chinese Medicine exerts overall clinical benefits through a multi-component and multi-target approach. In this study, we used the previously established co-infection model of Mycoplasma gallisepticum and Escherichia coli as a representative of complex diseases. A new combination consisting of 6 herbs were obtained by using network pharmacology combined with transcriptomic analysis to reverse screen TCMs from the Chinese medicine database, containing Isatdis Radix, Forsythia Fructus, Ginkgo Folium, Mori Cortex, Licorice, and Radix Salviae. The results of therapeutic trials showed that the Chinese herbal compounds screened by the target network played a good therapeutic effect in the case of co-infection. In summary, these data suggested a new method to validate target combinations of natural products that can be used to optimize their multiple structure-activity relationships to obtain drug-like natural product derivatives.